The basic-helix–loop–helix-PAS orphan MOP3 forms transcriptionally active complexes with circadian and hypoxia factors - Hogenesch, John B. (The National Academy of Sciences, 1998)
We report that MOP3 is a general dimerization partner for a subset of the basic-helix–loop–helix (bHLH)-PER–ARNT–SIM (PAS) superfamily of transcriptional regulators. We demonstrated that MOP3 interacts with MOP4, CLOCK, hypoxia-inducible factor 1α (HIF1α), and HIF2α. A DNA selection protocol revealed that the MOP3-MOP4 heterodimer bound a CACGTGA-containing DNA element. Transient transfection experiments demonstrated that the MOP3-MOP4 and MOP3-CLOCK complexes bound this element in COS-1 cells and drove transcription from a linked luciferase reporter gene. We also deduced the high-affinity DNA binding sites for MOP3-HIF1α complex (TACGTGA) and used transient transfection experiments to demonstrate that the MOP3-HIF1α and MOP3-HIF2α heterodimers bound this element, drove transcription, and responded to cellular hypoxia. Finally, we found that MOP3 mRNA expression overlaps in a number of tissues with each of its four potential partner molecules in vivo.